When to Graft the Incised Plate During TIP Repair? A Suggested Algorithm That may Help in the Decision-Making Process - Tariq O. Abbas (11247771) (2018)
Although more than 300 different techniques for hypospadias repair do exist, successful outcome depends mainly on the surgeon’s skills, availability of adequate tissue for urethral reconstruction and choice of the best suitable technique in each case. Significant advancements in the management of hypospadias occurred over the last few decades but there remains great controversy on how to select the best technical options (1). The general principle for hypospadias repair consists in the tubularization of ventral urethral plate, bringing the meatus all the way to the tip of the glans, depending on the presence of associated ventral penile curvature. Such accomplishment can be achieved with a single or staged procedure. In the most common scenario, distal hypospadias without curvature, tubularization of the urethral plate is the currently most frequently utilized approach (2). However simple tubularization is not always suitable, especially in narrow plates that could result in stenosis. Aiming to augment the plate dimensions Snodgrass, in 1998, popularized to simply deeply incise and tubularize the urethral plate, relying on epithelization/granulation of the raw dorsal urethra (3, 4). This procedure has been successful in a great number of cases, reason why it was quickly adopted worldwide. The mechanism of healing the incised plate is still open for discussion (5). Some authors believe there is complete re-epithelization with urothelium while others think that there is formation of granulation tissue that later is followed by gradual fibrosis of the area. This could be reason why some authors reported worse outcomes in narrow urethral plates, theorizing that most of the neourethra would be reconstructed based on a raw, current dorsal urethrotomy that gradually heals narrowing the segment (4, 6). Moreover, healing of a larger incised raw area of neourethra is unpredictable; it seems that this process may exert tension on the ventral suture line affecting its primary healing (7). In an attempt to improve healing of the neourethra after the TIP urethroplasty, grafting of the dorsal incised (GTIP) area using the inner prepuce has been described by several authors (8–10). Other Information Published in: Frontiers in Pediatrics License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3389/fped.2018.00326